2004
DOI: 10.1021/jp0467346
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Molecular Bromine from the Reaction of Ozone with Deliquesced NaBr Aerosol:  Evidence for Interface Chemistry

Abstract: The reaction of ozone with aqueous sodium bromide particles is investigated with a combination of aerosol chamber experiments, kinetics modeling, and molecular dynamics simulations. The molecular bromine production in the chamber experiments is approximately an order of magnitude greater than that predicted by known chemistry in the gas and bulk aqueous phases with use of a comprehensive computer kinetics model. Molecular dynamics simulations indicate that ozone has significant residence time at the air−soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
189
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(200 citation statements)
references
References 110 publications
11
189
0
Order By: Relevance
“…For the formation of molecular chlorine and bromine from aqueous halide aerosols, FinlaysonPitts and coworkers (4,30) have shown that the kinetics model predictions cannot be reconciled with the experimental results unless interfacial reactions are included. Specifically, the amount of molecular bromine formed upon reaction of ozone with the bromide ion in deliquesced sodium bromide aerosols is Ϸ10-fold larger than that predicted by known gas phase and bulk aqueous phase chemistry (30). When an interface reaction was included in the kinetics modeling, the amount of Br 2 formed was reasonably reproduced.…”
Section: Discussionmentioning
confidence: 99%
“…For the formation of molecular chlorine and bromine from aqueous halide aerosols, FinlaysonPitts and coworkers (4,30) have shown that the kinetics model predictions cannot be reconciled with the experimental results unless interfacial reactions are included. Specifically, the amount of molecular bromine formed upon reaction of ozone with the bromide ion in deliquesced sodium bromide aerosols is Ϸ10-fold larger than that predicted by known gas phase and bulk aqueous phase chemistry (30). When an interface reaction was included in the kinetics modeling, the amount of Br 2 formed was reasonably reproduced.…”
Section: Discussionmentioning
confidence: 99%
“…113,114 In contrast, the interface oxidation of Br À by O 3 does make a significant contribution to the formation of Br 2 in the dark. [115][116][117] Despite the progress on understanding the structure of salt solutions and the impacts on reactivity, much remains speculative. For example, the (OHÁ Á ÁCl) À complex proposed at the interface has not been observed, and the mechanism by which such a complex forms gaseous Cl 2 is not confirmed.…”
Section: Chemistry At the Interface Of Sea Salt Particlesmentioning
confidence: 99%
“…1 However, a combination of computational [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and experimental studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] has shown that ions can reside and even be enhanced at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 There is also evidence that the photolysis of species at the interface has higher quantum yields than those in the bulk. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] In short, interfacial kinetics and mechanisms may be significantly different compared to those in the bulk phase.…”
Section: Introductionmentioning
confidence: 99%